Handle Flags: Efficient and Flexible Selections for Inking Applications - , Tovi Grossman; Baudisch, Patrick; Hinckley, Ken (GI '09 Proceedings of Graphics Interface 2009, 2009)
There are a number of challenges associated with content selection in pen-based interfaces. Supplementary buttons to enter a selection mode may not be available, and selections may require a careful and error prone lasso stroke. In this paper we describe the design and evaluation of Handle Flags, a new localized technique used to select and perform commands on ink strokes in pen-operated interfaces. When the user positions the pen near an ink stroke, Handle Flags are displayed for the potential selections that the ink stroke could belong to (such as proximal strokes comprising a word or drawing). Tapping the handle allows the user to access the corresponding selection, without requiring a complex lasso stroke. Our studies show that Handle Flags offer significant benefits in comparison to traditional techniques, and are a promising technique for pen-based applications.